Microglia: Immune and non-immune functions - Borst, Katharina; Dumas, Anaelle Aurelie; Prinz, Marco (Immunity (Cambridge, Mass.), 2021)
As resident macrophages of the central nervous system (CNS), microglia are associated with diverse functions essential to the developing and adult brain during homeostasis and disease. They are aided in their tasks by intricate bidirectional communication with other brain cells under steady-state conditions as well as with infiltrating peripheral immune cells during perturbations. Harmonious cell-cell communication involving microglia are considered crucial to maintain the healthy state of the tissue environment and to overcome pathology such as neuroinflammation. Analyses of such intercellular pathways have contributed to our understanding of the heterogeneous but context-associated microglial responses to environmental cues across neuropathology, including inflammatory conditions such as infections and autoimmunity, as well as immunosuppressive states as seen in brain tumors. Here, we summarize the latest evidence demonstrating how these interactions drive microglia immune and non-immune functions, which coordinate the transition from homeostatic to disease-related cellular states. Understanding the diverse microglial interactions and functions taking place across neuropathology will pave the way to future treatment strategies. Borst, Dumas, and Prinz summarize our current understanding of microglial interactions with central nervous system (CNS)-resident and CNS-infiltrating cells during homeostasis and disease and highlight how this communication drives their immune and non-immune functions.